Contribution of the life‐history traits of a plant pathogen to the development of field epidemics. (15th April 2022) - Azzimonti, Gustavo; Papaïx, Julien; Lannou, Christian; Goyeau, Henriette
Abstract: The pathogenicity‐related traits of biotrophic plant pathogens are usually measured on the individual host plant, at the scale of a single pathogen life cycle, whereas epidemic development in the field encompasses a succession of cycles. It remains unclear which traits make the greatest contribution to pathogen fitness in the field and to epidemic severity. The objective of this study was to determine the contributions of elementary pathogenicity traits to epidemic development in field conditions. We challenged a set of wheat cultivars with three different leaf rust isolates, under both controlled and field conditions, in 3 consecutive years. Infection efficiency, latent period, lesion size, spore production per lesion and spore production capacity were measured in the greenhouse, whereas disease severity was measured in the field. Most, but not all, of the pathogenicity traits were related to each other. All traits contributed to epidemic development in the field, but to different extents. Surprisingly, lesion size and spore production per lesion were inversely correlated with epidemic severity. Conversely, there was a strong positive correlation between spore production capacity and pathogen fitness in the field, in accordance with the concept of propagule pressure as a strong determinant of invasion success. Severe epidemics were mostly associated with small lesions with a high spore production capacity, high infection efficiency and a short latent period. Abstract : Using a creative analytical approach, we investigated the links between epidemic severity, assessed in the field, and pathogen life‐history traits, as measured in the greenhouse at the scale of a single epidemic cycle.